Translation of lymphocyte mRNA for mouse colony stimulating factor. - Bleackley, R C (1983)
Poly A+ RNA has been purified from phorbol myristate acetate stimulated mouse EL4 cells. Translation, by microinjection into frog oocytes, gave biologically active interleukin 2 (IL2) and colony stimulating factor for granulocytes and macrophages (GM-CSF). These two mRNAs were separated by centrifugation through linear sucrose gradients. The sedimentation coefficients for IL2 and GM-CSF mRNAs were found to be 11.5S and 8S respectively. The clonal and cellular morphologies induced by the oocyte material corresponded to low concentrations of authentic GM-CSF.